Structure determination of the small ubiquitin-related modifier SUMO-1 - Bayer, Peter; Arndt, Andreas; Metzger, Susanne; Mahajan, Rohit; Melchior, Frauke; Jaenicke, Rainer; Becker, Jörg (Journal of molecular biology, 1998)
The recently discovered small ubiquitin-related modifier SUMO-1 belongs to the growing family of ubiquitin-related proteins involved in postranslational protein modification. Unlike ubiquitin, SUMO-1 does not appear to target proteins for degradation but seems to be involved in the modulation of protein-protein interactions. Independent studies demonstrate an essential function of SUMO-1 in the regulation of nucleo-cytoplasmic transport, and suggest a role in cell-cycle regulation and apoptosis. Here, we present the first three-dimensional structure of SUMO-1 solved by NMR. Although having only 18% amino acid sequence identity with ubiquitin, the overall structure closely resembles that of ubiquitin, featuring the ββαββαβ fold of the ubiquitin protein family. In addition, the position of the two C-terminal Gly residues required for isopeptide bond formation is conserved between ubiquitin and SUMO-1. The most prominent feature of SUMO-1 is a long and highly flexible N terminus, which protrudes from the core of the protein and which is absent in ubiquitin. Furthermore, ubiquitin Lys48, required to generate ubiquitin polymers, is substituted in SUMO-1 by Gln69 at the same position, which provides an explanation of why SUMO-1 has not been observed to form polymers. Moreover, the hydrophobic core of SUMO-1 and ubiquitin is maintained by conserved hydrophobic residues, whereas the overall charge topology of SUMO-1 and ubiquitin differs significantly, suggesting specific modifying enzymes and target proteins for both proteins.